Togo - Dirk Kohnert (Africa Yearbook Volume 1: Politics, Economy and Society South of the Sahara in 2004, 2005)
The roadmap for democratisation and economic liberalisation, negotiated with the EU as a precondition for resuming aid, dominated foreign and domestic politics. Opposition parties entered the new national dialogue on reconciliation only reluctantly in view of the authoritarian attitudes of the government. Rumours about the deteriorating health of the head of state, Gnassingbé Eyadéma, fuelled speculation about his succession. At the end of the year, he announced the dissolution of parliament and early elections in the first half of the next year. Socioeconomic development continued to suffer from the ongoing political crisis. – – Der mit der EU ausgehandelte Fahrplan für Demokratisierung und wirtschaftliche Liberalisierung als Voraussetzung für die Wiederaufnahme der Hilfe dominierte die Außen- und Innenpolitik. Die Oppositionsparteien traten angesichts der autoritären Haltung der Regierung nur zögerlich in den neuen nationalen Dialog zur Versöhnung ein. Gerüchte über den sich verschlechternden Gesundheitszustand des Staatschefs Gnassingbé Eyadéma heizten Spekulationen über seine Nachfolge an. Ende des Jahres kündigte er die Auflösung des Parlaments und vorgezogene Neuwahlen in der ersten Hälfte des nächsten Jahres an. Die sozioökonomische Entwicklung litt weiterhin unter der anhaltenden politischen Krise.
Additional information: Author's version
Keywords: F35; F54; N47; Z13; 330; Togo; Africa-Yearbook 2004